DETERMINATION OF READINESS OF MEANS OF RADIO ENGINEERING THE FLIGHTS FUNCTIONING IN AN UNSTABLE SITUATION - V. E. Emelyanov; M. E. Solozobov (Научный вестник МГТУ ГА, 2016)
The article gives the model of evaluating the coefficient of Radio Systems availability, which is based on the batsesovsky approach. And the possibility of its use for various functions of uptime distribution is shown.